(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Six stabilizing media consisting of peptone, lactose, sucrose, lactalbumin hydrolyzate, and gelatin were tested for their effectiveness in stabilizing the associated vaccine against peste des petits ruminants and sheep pox at lyophilization and storage. The effectiveness of the associated vaccines containing various stabilizing composition was evaluated by the level of the biological activity of the viruses, after their lyophilization and storage in different temperature-time regimes (minus 20°C, 4°C, (20–22)°C and (35–37)°C for 12 months., 7 days and 5 days, respectively) using specific sera. The control was the vaccine, dried without a protective environment. As a result of the research, it was established that a complex medium consisting of peptone-lactose at a final concentration of 3% and 2%, respectively, are effective stabilizers in the lyophilization and storage of the associated vaccine against peste des petits ruminants and sheep pox.